(untitled) (Bangladesh Journal of Botany, 2024)
The present investigation was undertaken with the objective of evaluation and identification of sugarcane clones for high yield, quality and its contributing traits in plant and ratoon crops. The study consists of three evaluation trials viz., Advanced Varietal Trial- plant-I (AVT-I), Advanced Varietal Trial-Plant-II (AVT-II) and AVT- Ratoon. All the three experiments consists of five test clones viz., CoA 12321, CoA 12322, CoA 12323, CoOr 12456 and CoV 12356 and three standards (Co 6907, CoC 01061, CoA 92081). Observations were recorded for number of tillers (x1000/ha), number of millable cane (x1000/ha), stalk length (cm), stalk diameter (cm), single cane weight (kg), cane yield (t/ha), brix (%), purity (%), sucrose (%), CCS (%) and CCS yield (t/ha). The results revealed that, among the test clones CoA 12322 and CoA 12321 registered the higher cane yield and CCS yield. The clone CoV 12356 recorded better performance for quality traits viz., sucrose per cent, purity per cent and CCS per cent. Hence these three clones may be promoted for further evaluation trial and could be released as new sugarcane variety suitable for east coast zone of India. Bangladesh J. Bot. 53(4): 1001-1009, 2024 (December)